HUBUNGAN ANTARA SELF-DISCLOSURE DAN RELIGIUSITAS DENGAN KOMITMEN PERNIKAHAN PADA ISTRI PELAUT TNI-AL - Rizki Amelia; M. Zainal Abidin; Windah Riskasari (Jurnal Psikologi Poseidon, 2018)
TNI-AL sailor's wife must be prepared if the husband left to sail, because it is a consequence. Although the left sailed, sailor's wife must believe and keep the marriage to her husband even when there are no nearby. The attitude of keeping the marriage is a form of marriage commitment. This study measures: (1) The relationship between self-disclosure with the commitment of marriage, (2) The relationship between religiosity and marriage commitment. This research method using quantitative methods, survey and analysis of data correlation with the analysis of product moment. The subject of this research is the wife of TNI-AL sailors who were in B Flats Eastern Fleet Surabaya totaling 135 people. The results showed: (1) There is a positive and significant relationship between self-disclosure with the commitment of marriage with sig is less than 0.05, (2) There is a positive and significant relationship between religiosity and commitment of marriage with sig is less than 0.05.